Subretinal Hyperreflective Material Imaged With Optical Coherence Tomography Angiography - Kunal K. Dansingani (2018)
© 2016 Elsevier Inc. Purpose The range of subretinal hyperreflective material (SHRM) seen in macular disease includes type 2 macular neovascularization, fibrosis, exudation, vitelliform material, and hemorrhage. The prognostic significance of SHRM has been evaluated retrospectively in clinical trials, but discriminating SHRM subtypes traditionally requires multiple imaging modalities. The purpose of this study is to describe optical coherence tomography angiography (OCTA) flow characteristics and artifacts that might help to distinguish SHRM subtypes. Design Validity analysis. Methods Patients with age-related macular degeneration (AMD), myopia, pachychoroid disease, and macular dystrophy, manifesting SHRM on optical coherence tomography (OCT), were recruited. Clinical chart review and multimodal imaging established the SHRM subtype. All patients underwent OCTA. OCT and OCTA images were examined together for (1) intrinsic flow, (2) retinal projection onto the anterior SHRM surface (strong, weak, absent), (3) retinal projection through SHRM onto retinal pigment epithelium (RPE), and (4) masking of choriocapillaris flow. Results Thirty-three eyes of 25 patients were included (type 2 neovascularization ×3; fibrosis ×4; exudation ×10; hemorrhage ×5; vitelliform ×17). Mean age per eye was 76 years (standard deviation: 12). Intrinsic flow was strongest in type 2 neovascularization. Subretinal fibrosis showed limited flow in residual large-caliber vessels and branches. Flow was not detected within foci of exudation, hemorrhage, or vitelliform lesions. Retina-SHRM surface projection was strongest onto smooth-surfaced SHRM and weaker onto exudation. Retinal projection was weakest on the surface of vitelliform lesions. Retina-RPE projection was masked by dense hemorrhage and vitelliform material. In compound SHRM, OCTA distinguished between vascular and avascular components. Conclusion Optical coherence tomography angiography can distinguish vascular from avascular SHRM components. OCTA artifacts may distinguish certain avascular SHRM components.